1990
DOI: 10.2527/1990.6861674x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buffer or DL-methionine with different amounts of supplemental corn on feed intake and nutrient digestion by Holstein steers consuming bermudagrass hay.

Abstract: Two latin squares were conducted to determine the effects on feed intake and nutrient digestion of adding a ruminal buffer or DL-methionine to supplemental ground corn for Holstein steers (avg BW of 286 and 222 kg in Exp. 1 and 2, respectively) with ad libitum access to bermudagrass hay. In Exp. 1, steers were not supplemented (control) or were given .5 (LC) or 1.0% BW/d (HC) of ground corn without or with .021% BW of sodium bicarbonate (B). Total DMI was 2.39, 2.71, 2.79, 2.81 and 2.98% BW (effects of supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
0
3
0
1
Order By: Relevance
“…Clark and Petersen (1988) and Gordon and Ashes (1984) observed that rumen microorganism populations were stimulated by Met supplementation. In previous studies, increased post ruminal supply of Met tended to gradually increase degradation of cellulose, hemicellulose (Li et al, 2007), DM, OM and CP (Hall et al, 1990;Huisman et al, 1988), but some reports suggested unaffected nutrients digestibility in cows or lambs as Met supple-AA added for sika deer fed low CP diet ACP, crude protein-adequate diet; DLN, crude protein-deficient (DCP) diet with 3 g/kg lysine; DLL, DCP with 3 g/kg lysine and 1 g/kg methionine; DLH, DCP with 3 g/kg lysine and 2 g/kg methionine; Lys, lysine; Met, methionine. ACP, crude protein-adequate diet; DLN, crude protein-deficient (DCP) diet with 3 g/kg lysine; DLL, DCP with 3 g/kg lysine and 1 g/kg methionine; DLH, DCP with 3 g/kg lysine and 2 g/kg methionine; BW, body weight; ADG, average daily gain; ADFI, average daily feed intake; G/F, gain to feed ratio.…”
Section: Discussionmentioning
confidence: 78%
“…Clark and Petersen (1988) and Gordon and Ashes (1984) observed that rumen microorganism populations were stimulated by Met supplementation. In previous studies, increased post ruminal supply of Met tended to gradually increase degradation of cellulose, hemicellulose (Li et al, 2007), DM, OM and CP (Hall et al, 1990;Huisman et al, 1988), but some reports suggested unaffected nutrients digestibility in cows or lambs as Met supple-AA added for sika deer fed low CP diet ACP, crude protein-adequate diet; DLN, crude protein-deficient (DCP) diet with 3 g/kg lysine; DLL, DCP with 3 g/kg lysine and 1 g/kg methionine; DLH, DCP with 3 g/kg lysine and 2 g/kg methionine; Lys, lysine; Met, methionine. ACP, crude protein-adequate diet; DLN, crude protein-deficient (DCP) diet with 3 g/kg lysine; DLL, DCP with 3 g/kg lysine and 1 g/kg methionine; DLH, DCP with 3 g/kg lysine and 2 g/kg methionine; BW, body weight; ADG, average daily gain; ADFI, average daily feed intake; G/F, gain to feed ratio.…”
Section: Discussionmentioning
confidence: 78%
“…Supplementation of lipid-coated Zn-Met and Mn-Lys chelates increased the digestibility of NDF in the reticulorumen compared with control in this study, and related reports are as follows. Hall et al (1990) found that providing Met to steers fed Bermudagrass hay and ground corn had a tendency to increase digestibility of total-tract NDF. Lodman et al (1990) noted there were numerical increases in in situ rate of DM and NDF disappearance in the rumen of gestating cows as a result of Met supplementation.…”
Section: Dm Intake and Digestibility Of Nutrientsmentioning
confidence: 97%
“…Conversely, Lodman et al (1990) noted only numerical increases in the extent and rate of DM and NDF digestion as a result of methionine and urea supplementation. Hall et al (1990) found that providing methionine to steers fed bermudagrass hay and ground corn had no significant effect on feed intake or digestion and only tended to increase total tract NDF digestion.…”
Section: Discussionmentioning
confidence: 90%